(3GdYdGbGJ GdYGeI aj GdCReGJ (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3JYQja GdYdGbGJ GdYGeI , eHGOFgG , SeGJgG , CgOGagG , hXGFagG h CSHGHgG , eaghe GdCReI h JOGYjGJgG , EOGQI GdGReGJ , OhQ LgGR GdYdGbGJ GdYGeI aj OLGd GdJNWjW ddCReGJ eY hLhO CSFdI ddefGbTI (B.s
(3eQGLY U(B.165s
Keywords: (3EOGQI GdGReGJs; (3GdGJUGds; (3GdCReGJs; (3GdYdGbGJ GdYGeIs